Auditor switching tendency in public companies of Jakarta Islamic Index (JII): An audit fee moderation perspective - Nazma Riska Zhafiraah; Harry Budiantoro (LPMP Imperium, 2026)
This study aims to analyze the effect of audit report lag, firm size, audit committee, and financial distress on auditor switching, with audit fee as a moderating variable. The research sample comprises 13 manufacturing companies in the miscellaneous industry sector listed on the Jakarta Islamic Index (JII) during 2019–2023, yielding 65 observations selected through purposive sampling. Logistic regression was employed for data analysis. The findings show that audit report lag and firm size have a significant negative effect on auditor switching, while financial distress has a significant positive effect. In contrast, the audit committee has no significant effect on auditor switching. Furthermore, audit fees do not moderate the relationship between audit report lag, firm size, audit committee, and financial distress with auditor switching. These results indicate that the decision to change auditors is more influenced by internal factors such as financial conditions and business complexity, as well as auditor rotation regulations, rather than the amount of audit fees paid. Public interest statements The originality of this study lies in its focus on sharia-compliant companies listed on the JII, which are rarely examined, thereby providing new insights into the dynamics of auditor switching in Indonesia's Islamic capital market.